2017
DOI: 10.1039/c7ta01372h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall PbS quantum dots: a facile and greener synthetic route and their high performance in luminescent solar concentrators

Abstract: Tributylphosphine-assisted greener synthesis of ultrasmall PbS quantum dots and their high performance in luminescent solar concentrator application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…An optical efficiency of 1.02% (claimed as a record) was reported for a G = 50 device (C = 0.50). [155] Sumner et al have reported a detailed analysis of optical losses in polymer LSCs based on NCs of CuInS 2 /CdS as emitters. LSCs of 7.5 × 7.5 × 0.10 cm of NC-containing poly(lauryl methacrylate-co-ethylene glycol) layer sandwiched between two 0.90 mm thick glass sheets led to an overall device thickness of 2.8 mm (G = 6.7).…”
Section: Emitters Based On Qds and Nanocrystalsmentioning
confidence: 99%
“…An optical efficiency of 1.02% (claimed as a record) was reported for a G = 50 device (C = 0.50). [155] Sumner et al have reported a detailed analysis of optical losses in polymer LSCs based on NCs of CuInS 2 /CdS as emitters. LSCs of 7.5 × 7.5 × 0.10 cm of NC-containing poly(lauryl methacrylate-co-ethylene glycol) layer sandwiched between two 0.90 mm thick glass sheets led to an overall device thickness of 2.8 mm (G = 6.7).…”
Section: Emitters Based On Qds and Nanocrystalsmentioning
confidence: 99%
“…These PbX [111] facets are undercoordinated and possess dangling bonds, where ligands will bind preferentially. Surface quantification studies have shown that PbX QDs have an excess of lead atoms, [47,48] which is significant in terms of ligand binding. It was shown that the number of ligands in oleate-capped PbX QDs correlates directly with the amount of excess surface Pb, with one ligand for each excess surface lead atom according to Moreels et al, [49] or one oleate ligand for every two surface Pb, according to Katsiev et al [50] The size of PbX QDs also influences their degradation dynamics.…”
Section: Seo 2 and Seomentioning
confidence: 99%
“…PbS can be size-tuned to absorb strongly over a wide range of wavelength on the electromagnetic spectrum thereby shifting its absorption edge into the near infrared region [33]. PbS has widely been used in several opto-electronic devices which include photovoltaic cells [34], sensors [35], thermoelectrics [36], photodetectors [37], diodes [38], catalyst [39], photoconductors [40] and solar concentrators [41]. We have previously reported the syntheses of PbS nanoparticles and thin films using xanthates as precursors [6,21].…”
Section: Introductionmentioning
confidence: 99%